Chromatin Structure and Function in Mosquitoes - Lezcano, Óscar M.; Sánchez-Polo, Miriam; Ruiz, José L.; Gómez-Díaz, Elena (Frontiers in Genetics, 2020)
The principles and function of chromatin and nuclear architecture have been extensively studied in model organisms, such as Drosophila melanogaster. However, little is known about the role of these epigenetic processes in transcriptional regulation in other insects including mosquitoes, which are major disease vectors and a worldwide threat for human health. Some of these life-threatening diseases are malaria, which is caused by protozoan parasites of the genus Plasmodium and transmitted by Anopheles mosquitoes, dengue fever, which is caused by an arbovirus mainly transmitted by Aedes aegypti, and West Nile fever, which is caused by an arbovirus transmitted by Culex spp. In this contribution, we review what is known about chromatin-associated mechanisms and the 3D genome structure in various mosquito vectors, including Anopheles, Aedes and Culex spp. We also discuss the similarities between epigenetic mechanisms in mosquitoes and the model organism Drosophila melanogaster, and advocate that the field could benefit from the cross-application of state-of-the-art functional genomic technologies that are well-developed in the fruit fly. Uncovering the mosquito regulatory genome can lead to the discovery of unique regulatory networks associated with the parasitic life-style of these insects. It is also critical to understand the molecular interactions between the vectors and the pathogens that they transmit, which could hold the key to major breakthroughs on the fight against mosquito-borne diseases. Finally, it is clear that epigenetic mechanisms controlling mosquito environmental plasticity and evolvability are also of utmost importance, particularly in the current context of globalisation and climate change.